PROBLEMS OF POLITICAL RELATIONS AND AFRICA COVER¬AGE IN ONLINE EDITIONS (Proceedings of Southern Federal University. Philology, 2013)
Boymassa B.Keywords: political processes, political and military conflicts, the modern state institutions in Africa, authoritarian political regimes, apartheid, military dictatorship, online journalism.The article reflects the current state of political processes in Africa (Liberia, Nigeria, Sierra Leone, Chad, Rwanda, etc.) and the practice of their coverage in the media, especially in the world of network media. According to the author, the current situation in Africa hinders the full participation of African countries in the global political cooperation and economic ties. As reported by the electronic media, the way out of this situation can be the integration of intra-African politics and economics. This idea is becoming more widespread and is more supported by political forces in Africa.